Examining the relationships between self-stigma, loneliness, depressive symptoms, and suicidal ideation among people with bipolar disorder - Piotr Świtaj; Paweł Grygiel; Joanna Leciak; Izabela Stefaniak; Sylwia Opozda-Suder; Marta Anczewska (Scientific Reports)
Abstract People diagnosed with bipolar disorder (BD) commonly experience self-stigma, which negatively affects various health outcomes. The aim of the present study was to elucidate the mechanisms through which self-stigma may contribute to suicidality among bipolar patients by investigating the mediating roles of loneliness and depressive symptoms. A total of 140 patients with BD were cross-sectionally assessed with self-report scales measuring self-stigma, loneliness, depressive symptoms and suicidal ideation, and with a clinician-rated scale evaluating overall psychopathology. Path analysis was used to analyze the data. Self-stigma was directly related to more severe loneliness, depressive symptoms and suicidal thoughts. There were also significant direct effects of loneliness on depressive symptoms and depressive symptoms on suicidal ideation. The direct effect of loneliness on suicidality was non-significant. The following indirect effects on suicidal ideation were found: from self-stigma via depressive symptoms, from loneliness via depressive symptoms and a sequential effect from self-stigma through loneliness and depressive symptoms. Our findings clearly indicate that interventions aiming to reduce the risk of suicide among people with BD should be comprehensive and take into account not only psychiatric symptoms, but also social context and the psychological aspects of living with this diagnosis.